1995
DOI: 10.1002/syn.890190405
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate/dopamine D1/D2 balance in the basal ganglia and its relevance to Parkinson' disease

Abstract: The recent availability of selective ligands for NMDA and AMPA receptors has enabled neuroscientists to test the hypothesis that Parkinson's disease is a glutamate hyperactivity disorder and hence treatable with glutamate antagonists. This review takes a critical look at the motor characteristics of this new class of drugs in rodent and primate models of parkinsonism and assesses the clinical potential and pitfalls of this radical new approach. Monotherapy of Parkinson's disease with glutamate antagonists appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(108 citation statements)
references
References 237 publications
4
103
0
1
Order By: Relevance
“…Although various antagonists of ionotropic glutamate receptors have proven to be good antiparkinsonian agents to reduce motor symptoms in preclinical studies, most of these compounds were found to induce debilitating nonmotor side effects in humans that were not assessed in animal studies, most likely due to the fact that AMPA and NMDA receptors are widely distributed and essential for normal brain functioning (Starr, 1995;Blandini and Greenamyre, 1998). Apart from amantadine, a serendipitously discovered NMDA receptor antagonist with good anti-dyskinetic properties (Factor and Molho, 1999), no other glutamate receptor antagonists are clinically used to treat PD.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…Although various antagonists of ionotropic glutamate receptors have proven to be good antiparkinsonian agents to reduce motor symptoms in preclinical studies, most of these compounds were found to induce debilitating nonmotor side effects in humans that were not assessed in animal studies, most likely due to the fact that AMPA and NMDA receptors are widely distributed and essential for normal brain functioning (Starr, 1995;Blandini and Greenamyre, 1998). Apart from amantadine, a serendipitously discovered NMDA receptor antagonist with good anti-dyskinetic properties (Factor and Molho, 1999), no other glutamate receptor antagonists are clinically used to treat PD.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…According to current theories of functional anatomy of basal ganglia (Albin et al 1989), the neurotransmitters dopamine and glutamate closely interact in the regulation of normal movements; whereas, an altered balance between dopamine-and glutamate-mediated neurotransmissions is thought to play a major role in the pathogenesis of movement disorders (Carlsson and Carlsson 1990;Lipton and Rosenberg 1994;Starr 1995). In Parkinson's disease because of the reduction of dopamine D 2 receptor-mediated inhibition of striatopallidal neurones, glutamate pathways within the indirect circuit become overactive (Alexander and Crutcher 1990;Gerfen et al 1990).…”
mentioning
confidence: 99%
“…The increased activity of the glutamatergic subthalamopallidal and, possibly, corticostriatal projections in animal models of PD led various groups to test the potential therapeutic benefits of ionotropic glutamate receptor antagonists in alleviating parkinsonian symptoms (see Starr, 1995;Blandini et al, 1996 for reviews). Systemic administration of NMDA and non-NMDA antagonists with subthreshold doses of L-DOPA or D2 dopamine receptor agonist has proven to ameliorate symptoms in primate models of PD (Starr, 1995;Blandini et al, 1996). Data reported in this review strongly suggest that interactions with metabotropic glutamate and GABA-B receptors may also have beneficial effects in PD.…”
Section: Metabotropic Glutamate and Gaba-b Receptors: Novel Therapeutmentioning
confidence: 99%
“…Data reported in this review strongly suggest that interactions with metabotropic glutamate and GABA-B receptors may also have beneficial effects in PD. Drugs interacting with these receptors are expected to influence the induction and progression of the symptoms of the disease without hampering the efficiency of fast glutamatergic and GABAergic synaptic transmission, thereby, reducing unwanted side effects commonly seen with drugs that target ionotropic receptors (Starr, 1995).…”
Section: Metabotropic Glutamate and Gaba-b Receptors: Novel Therapeutmentioning
confidence: 99%
See 1 more Smart Citation